Degenerative osteophyte causing acute locked knee in a young man: a case report - Khirul Ashar, Nur Ayuni; Hussin, Paisal; Mohd Nasir, Mohd Nizlan; Mawardi, Maliza (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2019)
Acute locked knee is usually caused by mechanical blockage. We report an unusual case of a locked knee due to tibial osteophyte in a young man following a sport injury. To the best of our knowledge, there has been no previous report describing the same etiology. This case report emphasizes the need for thorough history taking and careful assessment to aid us in the diagnosis. The findings made by arthroscopy confirmed our diagnosis.